A mechanosensitive ion channel controls touch-triggered stigma movement through manipulation of calcium signature in Torenia - Xuan Zhou; Binghou Li; Jiahuizi Li; Yufei Sun; Ruohan Xie; Tetsuya Higashiyama; Shi Xiao; Guorong Xin; Shihao Su (Nature Communications)
Abstract Rapid movements of plant structures triggered by mechanical force have been documented for centuries; however, how plant cells sense mechanical stimuli and generate rapid response remains unknown. Here we show the central role of a mechanosensitive channel gene in touch-triggered rapid stigma movement of Torenia fournieri. T. fournieri possesses a bilobed stigma sensitive to mechanical stimuli. Using live-cell calcium imaging, we detect that touch induces a wave of cytosolic calcium ([Ca2+]cyt) essential for stigma movement. Transcriptomic analysis reveals distinct gene expression profiles between the stigma and style, leading to the identification of the MscS-like gene JUE1, predominantly expressed in stigmas. Stigmas of jue1 mutants exhibit complete loss of touch-triggered movement, confirming its role as a key regulator in sensitive stigma movement. JUE1 is required for rapid propagation of the touch-induced [Ca2+]cyt, as cell-to-cell spreading of the [Ca2+]cyt wave is impaired in the jue1. To conclude, we report a plant mechanosensitive ion channel involved in touch-triggered organ movement by modulating calcium dynamics.